Neurotrophins and synaptic plasticity in the mammalian spinal cord - Mendell, Lorne M (Blackwell Science Inc, 2001)
The pathway mediating the monosynaptic stretch reflex has served as an important model system for studies of plasticity in the spinal cord. Its usefulness is extended by evidence that neurotrophins, particularly neurotrophin-3 (NT-3), which has been shown to promote spinal axon elongation, can modulate the efficacy of the muscle spindle-motoneurone connection both after peripheral nerve injury and during development. The findings summarized here emphasize the potential for neurotrophins to modify function of both damaged and undamaged neurones. It is important to recognize that these effects may be functionally detrimental as well as beneficial.